Rationality of Pocong Oath (Study on Residents of Lorong a Rahman, Rt 10/04, Kelurahan 1 Ilir, Ilir Timur II Sub-District Palembang City) - Randi Randi; Yoyok hendarso; Dadang Hikmah Purnama; Yosi Arianti; Yulasteriyani Yulasteriyani (Jurnal Scientia, 2024)
This research focuses on the rationality of the pocong oath on Lorong A Rahman residents, RT 10/04, Kelurahan 1 Ilir, Ilir Timur II District, Palembang City. The phenomenon of pocong vows has existed for a long time. The pocong oath is considered a local tradition of Indonesians to prove something true. This case has attracted much public attention in Indonesia because a pocong oath is still being carried out in the hustle and bustle of modernization. A total of 364,400 people liked the viral video on social media TikTok. The findings of this study show that the rationality of the pocong oath in Palembang City proves the truth and builds public trust. The method used in this study is qualitative research with three data collection techniques, namely in-depth interviews, conservation, and documentation.